INEXPERIENCE DE L’UNIVERSITE LAVAL DANS L’UTILISATION DES BANQUES D ’ INFORMATION / LAVAL UNIVERSITY’S EXPERIENCE WITH DATABASES - Francoeur, R.; Loranger, E.; Gamache, A. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see PDF